"They need to be able to have walked in our shoes": What people with intellectual disability say about National Disability Insurance Scheme planning. Issue 1 (2nd January 2019) - Collings, Susan; Dew, Angela; Dowse, Leanne
ABSTRACT: Background: Planning is a key mechanism by which the Australian National Disability Insurance Scheme (NDIS) ensures individuals with disability have choice and control over supports. People with intellectual disability will comprise the largest NDIS participant group and many will need assistance to engage in planning. In order to respond effectively, NDIS planners must understand the decision-making support required by individuals. Method: Focus groups were conducted with 9 adults with intellectual disability living in an NDIS trial site to explore their experiences of NDIS planning. Results: Thematic analysis identified 6 themes related to good planning experiences for people with intellectual disability: preparation, learning from mistakes, personal growth, and having a credible, consistent, and disability-aware planner. Conclusions: Participants who developed a trusting relationship with a planner used planning to increase independence and social participation. Planner skills, particularly communication and sector knowledge, and attributes such as warmth and openness created trust.